SU(3) Spin–Orbit Coupled Rotating Bose–Einstein Condensate Subject to a Gradient Magnetic Field - Chen, Guang-Ping; Tu, Pu; Qiao, Chang-Bing; Zhu, Jin-Xia; Jia, Qi; Zhang, Xiao-Fei (Frontiers in Physics, 2021)
We consider a harmonically trapped rotating spin-$1$ Bose-Einstein condensate with SU(3) spin-orbit coupling subject to a gradient magnetic field. The effects of SU(3) spin-orbit coupling, rotation, and gradient magnetic field on the ground state structure of the system are investigated in detailed. Our results show that the interplay among SU(3) spin-orbit coupling, rotation, and the gradient magnetic can results a variety of ground states, such as vortex ring, clover-type structure, and so on. The numerical results agree well with our variational analysis.